Academic Advising Session: The Perspective of Students and Advisors - Nurhaeni Nurhaeni (Jurnal Pendidikan Edutama, 2022)
Abstract : This research aimed to explore the perspective of students and academic advisors on their advising session that had been going so far. The method applied descriptive analysis since it was intended to set out the perspective of the research participants. Questionnaire was distributed to 103 university students of a study program. Afterwards, interview was conducted to five students and academic advisors for further clarification. The findings of this research revealed that both students and academic advisors admitted that the advising session was not yet as effective as what they had hoped for. They mentioned overlapping schedules and lacking of students’ motivation as parts of the reasons the advising session was not yet effective. For the future, the students and academic advisors both agreed that they need to create more communication and closer connection to have a better advising session.   Keyword: Academic Advising Session, Academic Advisor, StudentsAbstrak :Penelitian ini bertujuan untuk mengeksplorasi perspektif mahasiswa dan penasehat akademik terkait sesi pertemuan akademik yang telah mereka jalankan. Metode yang digunakan merupakan analisis deskriptif mengingat penelitian ini akan menjabarkan perspektif para responden. Angket didistribusikan kepada 103 mahasiswa dari sebuah program studi. Setelah itu, wawancara dilakukan kepada lima mahasiswa dan penasehat akademik untuk klarifikasi yang lebih jauh. Temuan penelitian ini menunjukkan bahwa mahasiswa dan penasehat akademik mengakui bahwa sesi pertemuan akademik belum seefektif yang mereka harapkan. Mereka menyebutkan bahwa kesamaan ketidaksesuaian jadwal dan kurangnya motivasi mahasiswa sebagai bagian alasan sesi pertemuan akademik belum efektif sesuai dengan harapan. Untuk ke depannya, mahasiswa dan pembimbing akademik sepakat bahwa mereka harus menciptakan lebih banyak komuniasi dan hubungan yang lebih dekat agar terciptanya sesi pertemuan akademik yang lebih baik.Kata kunci: Sesi Pertemuan Akademik, Penasehat Akademik, Mahasiswa